Knowledge about Byssinosis and the Use of Face-Masks - Respati, Titik; Ibnusantosa, Ganang; Rachmawati, Meike (Global Medical & Health Communication (GMHC), 2013)
Abstract The development of textile industry in Indonesia can potentially increase some occupational diseases that caused by waste products. One of those waste products from textile industry is cotton dust, which can cause byssinosis. There are several ways to reduce cotton dust exposure, such as using face mask. This research aim to describe the relationship between employees knowledgeÂ  about byssinosis with face mask utilization in spinning department of a textile factory.This research is a descriptive study with cross sectional approach. The subjects of this research are employees working on Spinning Department. Data gathered using questionnaire about byssinosis and the habit of using face mask.The result of this research shows that 52 (78.79%) of 66 respondents have excellent knowledge about byssinosis, meanwhile the other 14 (21.21%) show just enough knowledge. Almost all wear a face mask during working hour (92.42%). The result of chi square method shows that the relation between employees knowledge about byssinosis and face mask utilization is really weak (p=0,001, contingency coefficient = 0,381). The result of this research indicates that besides knowledge of byssinosis, there are other factors that can affect face mask utilization. Key word: Byssinosis, knowledge, face-masks